UNDERSTANDING UNIVERSITY UNDERGRADUATES’ ATTRIBUTION STYLES IN ACADEMIC PROCRASTINATION - Samson, AJAYI Oluwagbemiga (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
The study investigated university undergraduates’ attribution styles in academic procrastination. It further analyzed specific responses of the undergraduates’ academic procrastination based on attribution styles. This study adopted a survey design of correlational type. The sample size for the study comprised 1,800 university undergraduates selected through the use of a multistage sampling process. A researcher designed a questionnaire titled: Paradigm Model of Academic Procrastination Questionnaire (PMAPQ). Items in PMAPQ were generated based on the outcome of a grounded theory of procrastination as reported by Schraw, Wadkins, and Olafson (2007). This instrument was pilot-tested on 40 university undergraduates, using an internal consistency approach; a Cronbach’s Alpha value of 0.78 was obtained. Data were analyzed using mean, percentage, and charts. Results revealed that 48.4% of the students attributed procrastination in academics to task-related characteristics, 27.3% attributed procrastination to self-related characteristics while 24.3% attributed their procrastination in academic task to teachers related characteristics. Results further showed that 84.03% of the students who attributed procrastination to task-characteristics procrastinated when the task is not their priority; 84.80% of those with self-related characteristics attribution procrastinated when the task is boring while 79.21% of those with teacher-related characteristics attribution procrastinated when course instructors give clear instruction on the task to be done. The study concludes that university undergraduates in Southwest Nigeria attribute their procrastinatory behaviors more to task and self-characteristics than teacher-related characteristics. The study, therefore, recommends that the undergraduates need to be taught how to be more proactive in their learning/study habits with adequate skills in self-regulated learning to tackle the incidence of academic procrastination.